FV 16 Brain arousal regulation as response predictor for antidepressant therapy in major depression. Issue 10 (October 2017) - Schmidt, F.; Sander, C.; Hegerl, U.
Abstract : A tonically high level of brain arousal and its hyperstable regulation is supposed to be a pathogenic factor in major depression. Preclinical studies indicate that most antidepressants may counteract this dysregulation. Therefore, it was hypothesized that responders to antidepressants show (a) a high level of EEG-vigilance (an indicator of brain arousal) and (b) a more stable EEG-vigilance regulation than non-responders. In 65 unmedicated depressed patients 15-min resting-state EEGs were recorded off medication (baseline). In 57 patients an additional EEG was recorded 14 ± 1 days following onset of antidepressant treatment (T1). Response was defined as a ⩾ 50% HAMD-17-improvement after 28 ± 1 days of treatment (T2), resulting in 29 responders and 36 non-responders. Brain arousal was assessed using the Vigilance Algorithm Leipzig (VIGALL 2.1 0). At baseline responders and non-responders differed in distribution of overall EEG-vigilance stages (F2, 133 = 4.780, p = 0.009), with responders showing significantly more high vigilance stage A and less low vigilance stage B. Time-course of EEG-vigilance did not differ significantly between groups. Exploratory analyses revealed that responders showed a stronger decline in EEG-vigilance levels from baseline to T1 than non-responders (F2, 130 = 4.978, p = 0.005). Higher brain arousal level in responders to antidepressants supports the concept that dysregulation of brain arousal is a possible predictor of treatment response in affective disorders.